Research Note: Dietary phytase reduces broiler woody breast severity via potential modulation of breast muscle fatty acid profiles - Reagan N. Cauble; Elizabeth S. Greene; Sara Orlowski; Carrie Walk; Mike Bedford; Jason Apple; Michael T. Kidd; Sami Dridi (Poultry Science, 2020)
Woody breast (WB) myopathy is a major concern and economic burden to the poultry industry, and for which, there is no effective solution because of its unknown etiology. In a previous study, we have shown that phytase (Quantum Blue, QB) reduces the WB severity by 5% via modulation of oxygen homeostasis-related pathways. As WB has been suggested to be associated with lipid dysmetabolism, we aimed to determine the effect of QB on WB and breast muscle fatty acid profile. Male broilers were subjected to 6 treatments (96 birds/treatment): a nutrient adequate control group (PC), the PC supplemented with 0.3% myo-inositol (PC + MI), a negative control (NC) deficient in available P and Ca by 0.15 and 0.16%, respectively, the NC fed with QB at 500 (NC+500 FTU), and 1,000 (NC+ 1,000 FTU) or 2,000 FTU/kg of feed (NC+2,000 FTU). Woody breast and white striping scores were recorded, and fatty acid profiles were determined using gas liquid chromatography. Woody breast-affected muscles exhibited a significant higher incidence of white striping as liquid chromatography analysis reveals an imbalance of fatty acid profile in the breast of WB-affected birds with a significant higher percent of saturated fatty acids (SFA, myristic [14:0], pentadecanoic [15:0], and margaric [17:0]) and monounsaturated fatty acids (myristoleic [14:1], palmitoleic [16:1c], 10-trans-heptadecenoic [17:1t], oleic [18:1c9], and vaccenic [18:1c11]), and lower content of polyunsaturated fatty acids (PUFA) and omega-3 (P < 0.05). Quantum Blue at high doses (1,000 and 2,000 FTU) significantly reduces the percent of SFA and increases that of PUFA compared with the control group. In conclusion, WB myopathy seemed to be associated with an imbalance of fatty acid profile, and QB ameliorates the severity of WB potentially via modulation of SFA and PUFA contents.